Real Animals: Nationalism and the Practice of Zoological Research in China, 1900s–1930s - Frölich, Hajo (Comparativ, 2019)
When, in the early twentieth century, zoology as an academic subject was established in China, its first agents did all they could to distance themselves from earlier Chinese forms of researching animals. Instead, Chinese zoologists – many of whom had studied abroad – emphasized the complete novelty of their discipline and how it, like many other new branches of science, would contribute to making the Chinese nation “rich and strong” again. Yet by taking a closer look at China’s first scholarly journals devoted to zoology, this article demonstrates how in various ways, the new field was in fact also characterized by continuities and by references to “traditional” ways of studying animals in China. I suggest that such continuities should be read as conscious if understated attempts at self-assertion within an increasingly global scientific community. Thus, Chinese zoology doubtless was a hybrid undertaking far from having severed all connections to the country’s past. From the 1900s to the 1930s, however, both a cursory look as well as the rhetoric of Chinese zoologists suggested otherwise. This contradiction is explained by referring to the global political context as well as the role of nationalism.